The Influence of Parental Motivation on Interest in Learning Akidah Akhlak Among Female Students at Madrasah Qur’aniyah Al Husnayain Karanganyar - Mardianti, Radela; Suhadi, Suhadi (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2026)
This study addresses the limited empirical evidence on the influence of parental motivation on students’ interest in learning Akidah Akhlak, despite the family’s important role in shaping religious character and supporting religious education. It aims to assess students’ perceptions of parental motivation, describe their level of interest in Akidah Akhlak, and evaluate the strength of the influence of parental motivation on that interest among female students at Madrasah Qur’aniyah Al-Husnayain Karanganyar in the 2025/2026 academic year. Employing a quantitative, descriptive-correlational design, the study used total sampling to include all 35 students; data were collected via a Likert-type questionnaire and analyzed using descriptive statistics and Pearson Product-Moment correlation in SPSS 25. The findings show that parental motivation is at a moderately good level (mean = 55.8), while students’ interest in Akidah Akhlak is similarly moderate (mean = 55.5). Correlational analysis indicates a significant positive relationship between parental motivation and student interest (r = 0.592, p < 0.001), with parental motivation accounting for approximately 35% of the variance in interest. These outcomes highlight that both emotional and instructional parental involvement substantially contribute to students’ motivation and engagement in religious learning and open opportunities for follow-up research using mixed-methods or longitudinal designs to explore family involvement dynamics more deeply.